PENDEKATAN HYPER HEURISTIC DENGAN KOMBINASI ALGORITMA PADA EXAMINATION TIMETABLING PROBLEM - Supoyo, Vicha Azthanty; Muklason, Ahmad (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2019)
Generally, exam scheduling is still done manually and definitely will take a long time. Many researches have developed various studies to find a more appropriate strategy. Hyperheuristic was proposed in this study. In Hyperheuristic, Simple Random is used as a strategy for selecting low-level-heuristic while Hill Climbing and Simulation Annealing as move acceptance strategy. The Carter dataset is used as a test for the algorithms. We proposed testing datasets with a time limit of 15 minutes up to 1 hour and the results were compared with the research conducted by Carter et al (1996) as an initial study using that dataset. In addition, dataset, the number of iterations, and the time limit are as same as one of the literatures which will then be compared. The results obtained show that one pair of algorithms proposed in this study is better than the literature while other algorithms also provide significant results.